TINDAKAN KEPOLISIAN DALAM UPAYA PENANGGULANGAN PENYALAHGUNAAN NARKOTIKA DI DESA PETEMON KECAMATAN SERIRIT - Made Jody Januarta (Program Studi Ilmu Hukum Fakultas Hukum dan Ilmu Sosial Universitas Pendidikan Ganesha Singaraja, 2025)
This study examines the efforts of the Seririt Police Sector in combating drug abuse in Petemon Village, Seririt District, which increasingly threatens the social stability of the village. The purpose of this study is to describe and analyze both preventive and repressive police actions and to identify obstacles to their implementation. The method used is empirical legal research, with primary data obtained through field studies and interviews with members of the Seririt Police Station Narcotics Investigation Unit, victims, and community leaders, as well as secondary data from legal documents and related literature. The findings indicate that the police have adopted a holistic approach: education and targeted patrols as preemptive measures, and sting operations and raids as repressive actions, complemented by collaboration with traditional leaders, social institutions, and the use of information technology such as digital reporting apps and drug-sniffing dogs. However, the effectiveness of interventions is limited by inadequate detection infrastructure, low public participation, budget constraints, and the complexity of global distribution networks. The implications of this research emphasize the need to strengthen the technical capacity of police personnel, enhance inter-agency and community collaboration, and implement contextualized, sustainable education programs to ensure that drug control strategies at the village level are more responsive, sustainable, and focused on social reintegration.